The ways of psychological and pedagogical barriers overcoming between teachers and students during Covid-19 pandemic - Khudov, Hennadii; Tyurina, Valentina; Ovod, Yuliia; Kozyr, Marharyta; Chala, Anna; Khizhnyak, Irina (My University, 2020)
Пандемія COVID-19 вплинула на навчання та навчання у всьому світі. Як результат, школи та заклади вищої освіти використовують платформу електронного навчання, щоб замінити очне навчання. Електронне навчання висуває нові завдання, порівняно з традиційним, оскільки студентів відділяє від свого викладача екран комп’ютера. Установлено, що психолого-педагогічний бар’єр є перешкодою, що виникає для викладача в процесі його професійної діяльності, що знижує його ефективність. Виділено основні психолого-педагогічні бар’єри, що об’єднані в групи: завдяки особистим і професійним якостям викладача; спричинені фізичними та психологічними особливостями самого здобувача вищої освіти; визначається специфікою предмета взаємодії; спричинені несприятливими факторами соціального та матеріального середовища, в якому відбувається освітня взаємодія. Поглиблений аналіз типових бар’єрів, що потенційно виникають між викладачем та студентами, дає змогу визначити шляхи їх подолання. Окреслено психологічний портрет особистості, який потенційно створює бар’єри в міжособистісній взаємодії. У статті запропоновано шляхи подолання психологічних та освітніх бар’єрів між викладачами та студентами під час пандемії COVID-19. The COVID-19 pandemic has affected teaching and learning around the world. As a result, schools and higher learning institutions use the e-learning platform to replace face-to-face teaching and learning. E-learning presents new challenges when compared to a traditional classroom because students are separated from their instructor by a computer screen. It has been established that the psychological and pedagogical barrier is an obstacle arising for a teacher in the process of his professional activity, which reduces its effectiveness. The main psychological and pedagogical barriers are highlighted, which are combined into groups: due to the personal and professional qualities of the teacher; caused by the physical and psychological characteristics of the student himself; determined by the specifics of the subject of interaction; caused by unfavorable factors of the social and material environment in which educational interaction takes place. An in-depth analysis of typical barriers that potentially arise between a teacher and students makes it possible to determine ways to overcome them. A psychological portrait of a personality that potentially creates barriers in interpersonal interaction is outlined. The paper proposes the ways of overcoming psychological and educational barriers between teachers and students during the COVID-19 pandemic.
The ways of psychological and pedagogical barriers overcoming between teachers and students during Covid-19 pandemic / Hennadii Khudov, Valentina Tyurina, Yuliia Ovod, Marharyta Kozyr, Anna Chala, Irina Khizhnyak // Sys Rev Pharm – 2020. – № 11(11). – Р. 373–379. E-ISSN 0976-2779 E-ISSN 0975-845 Scopus
Keywords: COVID-19, пандемія, вчитель, студент, психолого-педагогічний бар’єр, подолання, електронне навчання; COVID-19, pandemic, teacher, student, psychological and pedagogical barrier, overcoming, e-learning